1998
DOI: 10.2337/diabetes.47.6.913
|View full text |Cite
|
Sign up to set email alerts
|

Leptin secretion from subcutaneous and visceral adipose tissue in women.

Abstract: Upper body obesity is a risk factor for type 2 diabetes. Little is known about the regulation of body fat distribution, but leptin may be involved. This study examined the secretion of leptin in subcutaneous and omental fat tissue in 15 obese and 8 nonobese women. Leptin secretion rates were two to three times higher in subcutaneous than in omental fat tissue in both obese and nonobese women (P < 0.0001 and P < 0.001, respectively). There was a positive correlation between BMI and leptin secretion rates in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
299
3
21

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 543 publications
(375 citation statements)
references
References 0 publications
52
299
3
21
Order By: Relevance
“…Furthermore, it has been shown that omental adipocytes contain less leptin mRNA and also secrete less leptin than subcutaneous adipocytes. 36 Our data thus con®rms the data of other investigators 37 ± 39 that abdominal fat, whether intra-or retro-peritoneal is not a determinant of peripheral plasma leptin.…”
Section: Body Fat Distribution In Women Es Tai Et Alsupporting
confidence: 54%
“…Furthermore, it has been shown that omental adipocytes contain less leptin mRNA and also secrete less leptin than subcutaneous adipocytes. 36 Our data thus con®rms the data of other investigators 37 ± 39 that abdominal fat, whether intra-or retro-peritoneal is not a determinant of peripheral plasma leptin.…”
Section: Body Fat Distribution In Women Es Tai Et Alsupporting
confidence: 54%
“…In agreement, CD40 mRNA levels in SAT increased with BMI and leptin mRNA level in a population of obese individuals. Like leptin [28,29], the CD40 mRNA level was 45% higher in SAT than in VAT. This could be due to larger fat cells in SAT than VAT [30], in line with the notion that leptin production is correlated with the degree of adipocyte development [31].…”
Section: Discussionmentioning
confidence: 90%
“…6,58,62 Leptin secretion in vitro is higher in subcutaneous adipocytes compared with visceral adipocytes and this secretion rate correlates well with serum leptin levels. 63 There are no studies that have compared regional leptin mRNA expression in subcutaneous adipose tissue; however, there are indirect suggestions that basal expression does not differ between abdominal and gluteofemoral fat. 64,65 Serum leptin increases in parallel with BMI and, interestingly, is higher in women.…”
Section: Leptinmentioning
confidence: 99%